after bounce 1: height = .7(2)
after bounce 2: height = .7 (.7)(2) = 2 (.7)^2
after bounce 3: height = 2 (.7)^3
...
after bounce n: height = .....
Suppose that a ball originally fell from a height of 2.0m and on each bounce the ball rises to 70% of the height from which it fell. Express the height reached, h , as a function of the number of bounces, n.
5 answers
How to formalize it into a equation using h as height, n as bounces
geeessh, what did I use for "height", what did I use for the number of bounces?
h=2(0.70)^n
correct